2000
DOI: 10.1021/bp000011w
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ion-Exchange Protein Separations Using a Vector Quantizing Neural Network

Abstract: In this work, a previously proposed methodology for the optimization of analytical scale protein separations using ion-exchange chromatography is subjected to two challenging case studies. The optimization methodology uses a Doehlert shell design for design of experiments and a novel criteria function to rank chromatograms in order of desirability. This chromatographic optimization function (COF) accounts for the separation between neighboring peaks, the total number of peaks eluted, and total analysis time. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The main optimized parameters considered in the development of sample protocols have been the reaction yield [35], the recovery [36][37][38] and the analytical signal intensity [39,40]. The majority of the studies on the improvement of the instrumental conditions focused generally on the optimization of the mobile phase [41][42][43][44][45][46][47]. Other instrumental parameters considered in a lesser extent are the flow rate [41,46,48], the analysis time [48], and column temperature [46].…”
Section: Liquid Chromatographymentioning
confidence: 99%
“…The main optimized parameters considered in the development of sample protocols have been the reaction yield [35], the recovery [36][37][38] and the analytical signal intensity [39,40]. The majority of the studies on the improvement of the instrumental conditions focused generally on the optimization of the mobile phase [41][42][43][44][45][46][47]. Other instrumental parameters considered in a lesser extent are the flow rate [41,46,48], the analysis time [48], and column temperature [46].…”
Section: Liquid Chromatographymentioning
confidence: 99%
“…NMDS is a single-objective optimization approach for searching the space of n-dimensional real vectors [ 20 ]. Earlier reports have shown that NMDS has been successfully applied for the modelling and optimization of a variety of chemical and biological processes [ 21 , 22 ]. Since it only uses the values of the objective functions without any derivative information (explicit or implicit), it falls into the general class of direct search methods [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complexities of real samples have showed the necessity of optimization of chromatographic separation conditions [2].…”
Section: Introductionmentioning
confidence: 99%